The Conformational State of the BTK Substrate PLCγ Contributes to Ibrutinib Resistance. Issue 5 (15th March 2022) - Joseph, Raji E.; Lowe, Jacques; Fulton, D. Bruce; Engen, John R.; Wales, Thomas E.; Andreotti, Amy H.
Graphical abstract: Highlights: Conformational preference of the cSH2-linker modulates PLCγ activity. Wildtype PLCγ adopts an optimal equilibrium between cSH2-linker associated with or dissociated from the adjacent cSH2 domain. Ibrutinib resistance mutations in PLCγ alter the conformational equilibrium of the cSH2-linker. In addition to the regulatory phosphorylation of Y783, the sPH domain regulates association of cSH2-linker with cSH2 domain. Mechanistic understanding of drug resistance will aid development of treatment strategies. Abstract: Mutations in PLCγ, a substrate of the tyrosine kinase BTK, are often found in patients who develop resistance to the BTK inhibitor Ibrutinib. However, the mechanisms by which these PLCγ mutations cause Ibrutinib resistance are unclear. Under normal signaling conditions, BTK mediated phosphorylation of Y783 within the PLCγ cSH2-linker promotes the intramolecular association of this site with the adjacent cSH2 domain resulting in active PLCγ. Thus, the cSH2-linker region in the center of the regulatory gamma specific array (γSA) of PLCγ is a key feature controlling PLCγ activity. Even in the unphosphorylated state this linker exists in a conformational equilibrium between free and bound to the cSH2 domain. The position of this equilibrium is optimized within the properly regulated PLCγ enzyme but may be altered in the context of mutations. We therefore assessed the conformational status of four resistance associated mutations within the PLCγ γSA and find that they each alter the conformational equilibrium of the γSA leading to a shift toward active PLCγ. Interestingly, two distinct modes of mutation induced activation are revealed by this panel of Ibrutinib resistance mutations. These findings, along with the recently determined structure of fully autoinhibited PLCγ, provide new insight into the nature of the conformational change that occurs within the γSA regulatory region to affect PLCγ activation. Improving our mechanistic understanding of how B cell signaling escapes Ibrutinib treatment via mutations in PLCγ will aid in the development of strategies to counter drug resistance.